Equity in Accessibility: Moving From Disparity to Insufficiency Analyses. Issue 4 (2nd October 2022) - Martens, Karel; Singer, Matan E.; Cohen-Zada, Aviv Lee
Abstract: Problem, research strategy, and findings: Many studies on transport equity have analyzed disparities in access to destinations between different population groups. In this study, we challenge this disparity approach and propose an alternative: analyzing accessibility insufficiencies. We argue that disparity analyses fall short on two accounts. First, they are based on group averages that inherently hide in-group variation. Second, they compare accessibility levels between groups without addressing whether these levels actually allow people to engage in daily activities. The proposed sufficiency approach avoids the former and addresses the latter by setting an explicit sufficiency threshold for accessibility. Empirical analyses for 49 of the 50 largest U.S. metropolitan areas confirmed the problematic nature of disparity analyses. In line with most literature, our disparity analyses show that disadvantaged groups are virtually always better served by transit than their more advantaged counterparts. Yet a systematic sufficiency analysis reveals large inequities in accessibility, regardless of the exact sufficiency threshold employed. Takeaway for practice: Our outcomes underscore the need for researchers and planning practitioners to move away from seemingly neutral disparity analyses toward equity analyses of insufficiencies. Though this move implies inevitably normative, and thus politically difficult, decisions, such analyses enable professionals to systematically identify transport inequities as input for regional transport plans. They may also be used to prioritize already proposed interventions based on their contribution to a reduction in accessibility insufficiencies.